Comparison of the Effectiveness of Cognitive Behavioral Therapy and Schema Therapy on Catastrophizing in Young Adults with Depressive Symptoms - Rahemi Nooran, Shily; Tizdast, Taher; Nasrolahi, Bita (Mental Health and Lifestyle Journal, 2026)
The present study aimed to compare the effectiveness of Cognitive Behavioral Therapy (CBT) and Schema Therapy (ST) on reducing catastrophizing in young adults with depressive symptoms. This applied study employed a quasi-experimental pretest–posttest design with a control group and a two-month follow-up period. The statistical population consisted of young adults diagnosed with depressive disorder who referred to counseling and psychological clinics in District 1 of Tehran between December 2024 and June 2025. From 224 eligible individuals, 45 participants meeting the inclusion criteria were selected using purposive sampling and randomly assigned to three groups: CBT (n = 15), ST (n = 15), and control (n = 15). Both intervention groups participated in eight structured group therapy sessions based on standardized treatment protocols, while the control group received no psychological intervention during the study period. Data were collected using validated self-report measures assessing depressive symptoms and catastrophizing. Statistical analysis was conducted using repeated measures analysis of variance (ANOVA) and Bonferroni post hoc tests in SPSS version 26, after verifying statistical assumptions. The results of repeated measures ANOVA indicated a significant main effect of time (p < 0.001) and a significant time × group interaction effect (p < 0.001) on catastrophizing, while the main effect of group was not statistically significant (p > 0.05). Bonferroni post hoc comparisons showed that both CBT and ST groups had significantly lower posttest catastrophizing scores compared to the control group (p < 0.001). However, no statistically significant difference was observed between the CBT and ST groups at posttest (p > 0.05). Pairwise comparisons across time demonstrated significant reductions in catastrophizing from pretest to posttest and from pretest to follow-up in both intervention groups (p < 0.001), with maintenance of treatment effects at follow-up. Both Cognitive Behavioral Therapy and Schema Therapy were effective in significantly reducing catastrophizing in young adults with depressive symptoms, and their effects were sustained over time; however, no significant difference was found between the two interventions in terms of overall effectiveness.